The Unseen Web, an Enormous Mass of Internet: Sundus Munir - SUNDUS MUNIR, SUNDUS MUNIR; Afrozah Nadeem, Afrozah Nadeem; Syeda Binish Zahra, Syeda Binish Zahra; sadia kousar, sadia kousar (International Journal for Electronic Crime Investigation, 2020)
Deep web is the part of the internet; it holds 99% of the internet rest of the internet is known as surface web and it is access able by standard search engines, Deep web is famous by different names and can be called as invisible and hidden web but it can’t be accessed by the standard exploratory engines this is due to the un indexed contents by common exploratory engines. Deep web content is invisible under HTML form. Deep web provides anonymous internet platform for hackers, government agencies and others. Due to this no one can trace the location of the user and don’t have any kind of information about the web surfing of the user. Dark web is the part of Deep web, the reason behind it commonly used for the black market i.e. Drug sale, ammunition sale, and many other illegal activities. It is the consist of millions of websites some of which are very informative. While on the other hand some of the portion is legal to visit and rest is illegal. These websites can be accessed by using the popular tools, i.e. TOR, I2P which provide anonymity. About 2 million people use the TOR browser to browse deep and dark web.